Hubungan Antara Kekuatan Otot Lengan Dengan Kemampuan Servis Panjang Dalam Permainan Bulu Tangkis Pada Peserta Didik SMP Negeri 2 Tondano - Samuel Sorongan Kumesan (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
This study aims to determine the relationship between arm muscle strength and long service ability in badminton among students of SMP Negeri 2 Tondano. Long service is one of the essential basic techniques to master in badminton, particularly in singles play. Arm muscle strength is suspected to be one of the determining factors for the success of the long service technique. This study uses a quantitative approach with a correlational method. The sample consisted of 20 students selected through a selection technique based on specific criteria such as body height and basic long service skills. The instruments used were a 30-second push-up test to measure arm muscle strength and a badminton long service accuracy test to assess long service ability. The correlation analysis showed a correlation coefficient value of r = 0.22, which falls into the low category, with a contribution of 4.84% to long service ability. The t-test result showed a t-count of 0.95, which is smaller than the t-table value of 2.101, indicating no significant relationship between arm muscle strength and long service ability. Therefore, other components such as wrist flexibility, stroke technique, and accuracy are considered dominant factors in achieving an effective long service.